2007
DOI: 10.1136/thx.2006.066241
|View full text |Cite
|
Sign up to set email alerts
|

Early growth and adult respiratory function in men and women followed from the fetal period to adulthood

Abstract: Background: While some studies suggest that poor fetal growth rate, as indicated by lower birth weight, is associated with poor respiratory function in childhood, findings among adults remain inconsistent. A study was undertaken to determine the association between early growth and adult respiratory function. Methods: A longitudinal birth cohort study was performed of 5390 men and women born full term and prospectively followed from the fetal period to adulthood. Weight at birth and infancy were recorded, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 45 publications
6
105
0
2
Order By: Relevance
“…236 development of airways and alveoli occurs in early life (37). Developmental adaptations in 238 fetal life and infancy due to early life adverse exposures might result in impaired lung growth 239 with smaller airways, decreased lung volume, and subsequently to an increased risk of 240 bronchopulmonary dysplasia, asthma or COPD (9,14,38). Previous studies suggest that 241 children with asthma already have a reduced lung function in the first months of life, and that 242 this deficit progresses into childhood and early adulthood (39,40).…”
Section: Early Growth Measures and Lung Function Outcomes 176mentioning
confidence: 99%
“…236 development of airways and alveoli occurs in early life (37). Developmental adaptations in 238 fetal life and infancy due to early life adverse exposures might result in impaired lung growth 239 with smaller airways, decreased lung volume, and subsequently to an increased risk of 240 bronchopulmonary dysplasia, asthma or COPD (9,14,38). Previous studies suggest that 241 children with asthma already have a reduced lung function in the first months of life, and that 242 this deficit progresses into childhood and early adulthood (39,40).…”
Section: Early Growth Measures and Lung Function Outcomes 176mentioning
confidence: 99%
“…All studies were in English and all 18 articles reported associations for FVC, while only 10 also reported FEV1/FVC. One article reported results from two different study populations (17) and five reported results for males and females separately (18)(19)(20)(21)(22), so the total number of comparisons was 24 for FVC and 14 for FEV1/FVC ( Figure E1). Birth weight was investigated in all 18 studies, whereas there was only one for weight at one year and another one for weight gain in the first year of life.…”
Section: Inclusion and Exclusion Of Studiesmentioning
confidence: 99%
“…In utero exposures, such as smoking, have been shown to influence the developing fetal lung (1). Variations in lung maturity and in genes known to be expressed during lung development, and birth weight, have been associated with childhood asthma, bronchopulmonary dysplasia (BPD), adult lung function, and with death from chronic obstructive airways disease in adult life (2)(3)(4). This highlights the need to understand variability in the course of prenatal lung development, as it may contain the imprint for life-long pulmonary function growth/decline, and the developmental origins of chronic lung disease.…”
mentioning
confidence: 99%